RETRACTED: Determination of the optimal amplitude of vibration behavior in the potato sorting machine - Umurzakov Akramjon; Sabirjanov Тalibjan; Okyulov Kamoliddin; Gaparov Kodir (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 538, 00001 (2024), https://doi.org/10.1051/e3sconf/202453800001